Molecular insight into the release of phosphate from dissolved organic phosphorus photo-mineralization in shallow lakes based on FT-ICR MS analysis. (15th August 2022) - Li, Xiaolu; Guo, Minli; Wang, Yi; Liu, Guanglong; Fu, Qinglong
Highlights: Phosphate released from dissolved organic phosphorus photo-mineralization; Relative abundance of DOP formulae with higher MW, DBE was photo-reduced; Oxy-aromatic-like formulae were photo-reduced while lipid-like formulae were produced; OH induced by DOM was mainly responsible for DOP photo-mineralization. Abstract: Dissolved organic phosphorus (DOP) is a key factor in the water eutrophication process because of its high potential bioavailability and inorganic phosphate (Pi) compensation ability through bio- and photo-mineralization. However, the research on the characterization and transformation of DOP is insufficient owing to their complex composition. This study investigates the release of dissolved Pi from DOP photo-mineralization in Lake Dong based on Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR MS) analysis. The results showed that the photo-release of dissolved Pi is spatially heterogeneous in Lake Dong and is consistent with the distribution of DOP concentration. The FT-ICR MS results showed that the simulated irradiation decreased the relative abundance (RA) of the DOP molecular formulae with higher molecular weight (MW) and higher double bond equivalence values (DBE), while the RA of DOP molecular formulae with lower MW and lower DBE value increased or remained. Besides, the total RA of lipid-like formulae increased from 49.09% to 55.90%, while the oxy-aromatic-like formulae decreased from 50.91% to 44.10%, suggesting that simulated irradiation would influence the potential bioavailability of DOP. As the main photolysis medium during DOP photo-mineralization, the hydroxyl radicals (∙OH) are mainly derived from dissolved organic matter (DOM) compared to the nitrate (NO3 − ) and iron ion (Fe 3+ ) in Lake Dong. These results are important in understanding the ability and mechanism of DOP photo-mineralization and provide suggestions for cycling phosphorus in eutrophic shallow lakes. Graphical abstract: Image, graphical abstract